Dynamic relationship of traditional soil restoration practices and climate change adaptation in semi-arid Niger - Abdourhimou Amadou Issoufou; Idrissa Soumana; Garba Maman; Souleymane Konate; Ali Mahamane (Heliyon, 2020)
Climate change increases the vulnerability of agrosystems to soil degradation and reduces the effectiveness of traditional soil restoration options. The implementation of some practices need to be readjusted due to steadily increasing temperature and lowering precipitation. For farmers, the best practice found, should have the potential to achieve maximum sustainable levels of soil productivity in the context of climate change. A study was conducted in South-West Niger to investigate the use of the suitable practice, through (i) a meta-analysis of case studies, (ii) using field survey and (iii) by using AquaCrop model. Results showed that the effects of the association zaï + mulch on crop yield was up to 2 times higher than control plots depending on climate projections scenario RCP 8.5 under which carbon dioxide (CO2) concentrations are projected to reach 936 ppm by 2100. The practice appeared to be an interesting option for enhancing crop productivity in a context of climate change. Concerning its ability, it offers the best prospects to reverse soil degradation in the study area. In addition, the simulation showed that this strategy was suitable for timely sowing and therefore confirmed scholars and farmers views. Furthermore, this practice is relatively more effective compared to the others practices. These results show that association zaï + mulch could be considered as the best practice that can participate to a successful adaptation to reduce risk from climate change at the same time by reducing the vulnerability of farmers in Southwest of Niger for now and even for the future.